Pengaruh Firm Size, Leverage, Growth Dan Liquidity Terhadap Corporate Cash Holding - Vinny Laurencia; Elizabeth Sugiarto Dermawan (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The main purpose of this study in to find the influence of firm size, leverage, growth and liquidity on corporate cash holding in a company empirically using secondary data. The secondary data used as the population in this study were taken from the annual financial reports of manufacturing companies listed on the IDX from 2017-2019 respectively. Researchers used purposive sampling technique which is a non-random sampling technique as a research technique. This study used 87 data from manufacturing companies with a total of 261 data for 3 year. Data processing techniques using multiple regression analysis what helped by SPSS program (Statistical Product and Service Solution) for Windows released 25 and Microsoft Excel 2016. The result of research shows that firm size has positive significant influence towards corporate cash holding, leverage has negative significant influence towards corporate cash holding, growth have no significant influence towards corporate cash holding, and liquidity have positive significant influence towards corporate cash holding.The implication of this study is to maintain an optimal level of cash holding in a company which is influenced by various factors.